Magnesium hydroxide recovery from magnesia waste by leaching and precipitation process - Kurama, H.; Ayvazoğlu Yüksel, G.; Hoşgün, Halit Levent (My University, 2013)
The objective of the study is to determine the recyclability of magnesia waste as a relatively pure magnesium hydroxide. In previous study, it was found that magnesium can readily soluble in HCl solution and both temperature difference and the concentration of solution strongly affect the reaction rates and the solution compositions. Therefore, present study is devoted to the precipitation of Mg(OH)2 from MgCl2 solution conducted with using NaOH and Ca(OH)2. The waste sample at first leached by using HCl and the leached solution is subsequently submitted to series of neutralizing steps under controlled pH to remove the acid soluble impurities such as Si, Fe, etc present in solution together with dissolved Mg. The importance of solution pH and type of the precipitation reactive used in precipitation stages were tested and discussed to find out their effect on the separation process. The test results showed that Mg(OH)2 can be obtained with a impurities level less than 2 %.
Recylex;Aurubis;Befesa;Berzelius Metall;Oschatz
7th European Metallurgical Conference, EMC 2013 -- 23 June 2013 through 26 June 2013 -- Weimar -- 99798
Keywords: Leaching; Magnesium hydroxide; Precipitation; Recycling